Does "Flattening the Curve" Affect Critical Care Services Delivery for COVID-19? A Global Health Perspective - Ramiro E. Gilardino (Kerman University of Medical Sciences, 2020)
During this coronavirus disease 2019 (COVID-19) global pandemic, nations are taking bold measures to mitigate the spread of Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections in order to avoid the overwhelming its critical care facilities. While these "flattening the curve" initiatives are showing signs of impeding the potential surge in COVID-19 cases, it is not known whether these measures alleviate the burden placed on intensive care units. Much has been made of the desperate need for critical care beds and medical supplies, especially personal protective equipment (PPE). But while these initiatives may provide health systems time to bolster their critical care infrastructure, they do little to protect the most essential element - the critical care providers. This article examines bolder initiatives that may be needed to both protect crucial health systems and the essential yet vulnerable providers during this global pandemic.